Backbone resonance assignments of the outer membrane lipoprotein FrpD from Neisseria meningitidis - Bumba, Ladislav; Sviridova, Ekaterina; Kutá Smatanová, Ivana; Řezáčová, Pavlína; Veverka, Václav (Biomolecular NMR assignments, 2014)
The iron-regulated FrpD protein is a unique lipoprotein embedded into the outer membrane of the Gram-negative bacterium Neisseria meningitidis. The biological function of FrpD remains unknown but might consist in anchoring to the bacterial cell surface the Type I-secreted FrpC protein, which belongs to a Repeat in ToXins (RTX) protein family and binds FrpD with very high affinity (K(d) = 0.2 nM). Here, we report the backbone (1)H, (13)C, and (15)N chemical shift assignments for the FrpD(43-271) protein that allow us to characterize the intimate interaction between FrpD and the N-terminal domain of FrpC.
Keywords: lipoproteiny; Bacterial Outer Membrane Proteins; Lipoproteins; Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární; proteiny vnější bakteriální membrány; Neisseria meningitidis; Amino Acid Sequence; sekvence aminokyselin